Recent Advances in Proteomics Research 2015
DOI: 10.5772/61776
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Dynamics with Heavy Water — Instrumentations, Data Analysis, and Biological Applications

Abstract: The quantitative assessment of the synthesis of individual proteins has been greatly hindered by the lack of a high-throughput nonradioactive method. We recently developed a method that we call proteome dynamics and software that enables high-throughput kinetic analyses of peptides on a proteome-wide scale. Previous studies established that oral administration of heavy water H O or deuterium oxide, D O is safe and well tolerated in humans. "riefly, a loading dose of H O, a nonradioactive isotope, is administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(36 citation statements)
references
References 89 publications
(128 reference statements)
2
32
0
2
Order By: Relevance
“…Kürzlich wurden auch experimentelle Protokolle zur Messung der Zellproliferation basierend auf dem Deuteriumeinbau aus D 2 Oinden Deoxyribose-Baustein von Purin-Deoxyribunukleotiden in der DNAt eilender Zellen beschrieben. [224] Angewandte Chemie Aufsätze Das SILK-Protokoll ("stable isotope labeled kinetic") ist ein Ansatz zur Untersuchung der nicht-natürlichen Anreicherung amyloider Plaques,d ie sich in den Gehirnen von Alzheimer-Patienten finden, sowie der zugehçrigen Wirkung von Alzheimermedikamenten, wobei die Produktions-und Abbauraten von b-Amyloidpeptiden nach der Verabreichung von [ 13 C]l-Leucin gemessen werden. [6,6-D 2 ]-d-Glukose wurde beispielsweise eingesetzt, um die hepatische Glukoseproduktionsrate zu messen [230] oder die Insulinsensitivitätu nd Glukoseeffektivitätb ei basalem Insulin im intravençsen Glukosetoleranztest (IVGTT) zu bestimmen.…”
Section: Anwendungen Stabiler Isotope In Der Klinischenunclassified
See 1 more Smart Citation
“…Kürzlich wurden auch experimentelle Protokolle zur Messung der Zellproliferation basierend auf dem Deuteriumeinbau aus D 2 Oinden Deoxyribose-Baustein von Purin-Deoxyribunukleotiden in der DNAt eilender Zellen beschrieben. [224] Angewandte Chemie Aufsätze Das SILK-Protokoll ("stable isotope labeled kinetic") ist ein Ansatz zur Untersuchung der nicht-natürlichen Anreicherung amyloider Plaques,d ie sich in den Gehirnen von Alzheimer-Patienten finden, sowie der zugehçrigen Wirkung von Alzheimermedikamenten, wobei die Produktions-und Abbauraten von b-Amyloidpeptiden nach der Verabreichung von [ 13 C]l-Leucin gemessen werden. [6,6-D 2 ]-d-Glukose wurde beispielsweise eingesetzt, um die hepatische Glukoseproduktionsrate zu messen [230] oder die Insulinsensitivitätu nd Glukoseeffektivitätb ei basalem Insulin im intravençsen Glukosetoleranztest (IVGTT) zu bestimmen.…”
Section: Anwendungen Stabiler Isotope In Der Klinischenunclassified
“…Transaminierungsprozess zur Deuteriummarkierung von Proteinend urch D 2 O. [224] Angewandte Chemie Aufsätze 1786 www.angewandte.de Das SILK-Protokoll ("stable isotope labeled kinetic") ist ein Ansatz zur Untersuchung der nicht-natürlichen Anreicherung amyloider Plaques,d ie sich in den Gehirnen von Alzheimer-Patienten finden, sowie der zugehçrigen Wirkung von Alzheimermedikamenten, wobei die Produktions-und Abbauraten von b-Amyloidpeptiden nach der Verabreichung von [ 13 C]l-Leucin gemessen werden. [232] Ein duales SILK-Protokoll, bestehend aus der oralen Gabe von Deuteriumoxid zusammen mit der konstanten Infusion von Natrium[1-13 C]acetat, wurde an zwçlf Te stpersonen angewendet, um die anteiligen und absoluten Syntheseraten von Cholesterin zu messen.…”
Section: Anwendungen Stabiler Isotope In Der Klinischenunclassified
“…Stable isotopes have been used successfully to determine the biosynthetic pathways of different molecules. Of these, 13 C, 15 N, and 18 O have been applied to understand the mechanisms of bacteriochlorophyll and Chl biosynthesis (6,10,11). The 18 O in H 2 18 O and 18 O 2 has been used to investigate the origin of the oxygen atoms in Chl a, b, and d (12)(13)(14).…”
mentioning
confidence: 99%
“…The fifth oxygen atom at the C13 1 -oxo group of Chl a comes from molecular oxygen (O 2 ) through an oxygenase-type reaction in all oxygenic photosynthetic organisms (6). Using 18 O-labeling technology, it was further revealed that the sixth oxygen atom at the C7 formyl group of Chl b is derived from O 2 and not from water (12). The sixth oxygen atom of the formyl group at the C3 position in Chl d is also derived from O 2 through an oxygenase-type reaction mechanism, although the enzyme directly involved in the reaction is yet to be characterized (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation